2001
DOI: 10.1006/viro.2000.0731
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Targeting of Walleye Dermal Sarcoma Virus Orf A (rv-Cyclin)

Abstract: Walleye dermal sarcoma virus (WDSV) induces tumors and allows or possibly directs tumor regression. WDSV encodes a putative cyclin homologue, Orf A, and six variant Orf A transcripts have been identified. Northern analysis indicated that a 3.3-kb transcript, encoding full-length Orf A, is the predominant transcript in developing, but not regressing, tumors. Three Orf A proteins, one full-length and two amino-truncated forms, were expressed in mammalian and piscine cells, and their intracellular locations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 38 publications
2
56
1
Order By: Relevance
“…Recently, it was suggested that only amino-truncated forms of the WDSV cyclin protein are produced in regressing tumors (61,67). The data in these reports show, in agreement with earlier observations (41,42,61), that an mRNA encoding the full-length WDSV cyclin protein is the predominant orf-A transcript in developing tumors.…”
Section: Viral Gene Expression In Developing and Regressing Lesionssupporting
confidence: 88%
See 3 more Smart Citations
“…Recently, it was suggested that only amino-truncated forms of the WDSV cyclin protein are produced in regressing tumors (61,67). The data in these reports show, in agreement with earlier observations (41,42,61), that an mRNA encoding the full-length WDSV cyclin protein is the predominant orf-A transcript in developing tumors.…”
Section: Viral Gene Expression In Developing and Regressing Lesionssupporting
confidence: 88%
“…The data in these reports show, in agreement with earlier observations (41,42,61), that an mRNA encoding the full-length WDSV cyclin protein is the predominant orf-A transcript in developing tumors. In contrast with earlier reports, the full-length orf-A mRNA was not detected in regressing tumors when a probe homologous to the region of the mRNA encoding the amino terminus of the WDSV cyclin was used; see below (67). Alternatively spliced mRNAs encoding aminotruncated forms of the WEHV1 or WEHV2 rv-cyclins have not been detected in regressing lesions (42) and therefore do not appear to be used by the WEHVs during tumor development and regression.…”
Section: Viral Gene Expression In Developing and Regressing Lesionscontrasting
confidence: 59%
See 2 more Smart Citations
“…Only A1 contains the entire orfa reading frame. During tumor development, only transcript A1 and a transcript containing orfb can be detected by Northern analysis (37,38). The OrfA protein, expressed in cell culture, can inhibit the activity of the WDSV promoter (47), and it is localized in the nucleus in interchromatin granule clusters (IGCs) (38).…”
mentioning
confidence: 99%